The conceptual modeling of serials of IFLA LRM and PRESSoo models: contributions to cataloging theory and practice - Oliveira, Rhuan Henrique Alves de [UNESP]; Castro, Fabiano Ferreira de (Univ Federal Santa Catarina, 2024)
Objective: To Present a theoretical and methodological framework, built from the identification and presentation of the state of the art of IFLA LRM and PRESSoo's conceptual modeling of serials, mapping their contributions to the description and control of these resources in information systems. Methods: This research adopts the Systematic Literature Review as its method, which is made up of a structured body of protocols, steps and pre-defined criteria, which guarantee high and verifiable quality, focusing on its reproducibility by other researchers. Results: It was verified that PRESSoo has a granular and exhaustive modeling of serials with classes and properties that cover the entire scope of bibliographic information contained in these resources. Using the Object-Oriented modeling language, the model allows the structuring of event-centric classes, and being flexible, it declares properties that allow an object-centric approach. IFLA LRM, in turn, has a modeling with greater emphasis on the structure of entities, not being as exhaustive in declaring attributes and relationships for serials; however, providing the integration of other models, through expansion mechanisms of its own. Conclusions: It was found that IFLA LRM and PRESSoo models, based on a syntactic and semantic restructuring, can unify and consolidate cataloging theory and practice regarding serials, providing a conceptual structures that provides solutions to the complex problems of these resources and a common and exhaustive understanding of this domain.
Keywords: Cataloging; Metadata; Conceptual models; Serials